In weed we trust: Embodied everyday resistance. (July 2021) - Makoni, Busi
Abstract: Grounded in multimodality, this study explores how t-shirt inscriptions prevalent among students are used to challenge institutional rules prohibiting the consumption of cannabis on college campuses. Findings from a qualitative study involving the purposive sampling of college students' t-shirt inscriptions indicate that these serve as a space where text and images related to different genres are repurposed to produce new meanings. This is achieved using two tropes—1) the truth-value of scientific evidence as irrefutable and 2) American national symbols of freedom and patriotism—to discursively construct the illegality of cannabis-smoking as part of the broader social relations of inequality. Highlights: Global interest on legalizing weed has strong support among college students. T-shirt inscriptions challenge institutional rules against smoking of weed. Two main tropes used are truth-value of science and symbols of American freedom. Students seem to create their own imaginary truth regime, privileging good grades. These discursively construct weed's illegality as part of broader social inequality.